2004
DOI: 10.1111/j.1471-4159.2004.02370.x
|View full text |Cite
|
Sign up to set email alerts
|

17beta‐estradiol protects oligodendrocytes from cytotoxicity induced cell death

Abstract: During pregnancy, changes in circulating levels of hormones, including estrogens, correlates with a significant decrease in the relapse incidence in women with Multiple Sclerosis (MS). In the present study, we demonstrate that both primary and cell line cultures of rat oligodendrocytes express the estrogen receptor (ER)-a and ERb estrogen receptors in the cytosol and nucleus, and that nuclear compartmentalization becomes more pronounced as the cells mature. Moreover, 17b-estradiol significantly decreases the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
77
2
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 87 publications
6
77
2
1
Order By: Relevance
“…The level of ERa (but not ERb) mRNA is higher in female than male OLs (Takao et al, 2004). However, in the present work, the staining pattern of OLs by immunohistochemistry (Fig.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations
“…The level of ERa (but not ERb) mRNA is higher in female than male OLs (Takao et al, 2004). However, in the present work, the staining pattern of OLs by immunohistochemistry (Fig.…”
Section: Discussioncontrasting
confidence: 69%
“…Moreover, OL membranes also had a weakly stained band of 65 kDa. Takao et al (2004) reported that rat brain had 65 and 60 kDa forms of ERa. Smaller ERa isoforms have also been reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the ability of estrogens to antagonize these glutamate-induced reductions in protein phosphatases suggests that this action is common to estrogen protection in both oxidative stress and excitotoxicity in neurons. In addition, experimental data from various studies have shown not only the ability of estrogen to protect glial cells from various toxins (Bishop and Simpkins, 1994;Haghighat et al, 2004;Takao et al, 2004) but also the mediation of glial cells in estrogen neuroprotection (Sortino et al, 2004;Wynne and Saldanha, 2004). Therefore, it is important to understand the mechanism of estrogen actions in both neurons and glia.…”
Section: Discussionmentioning
confidence: 99%